Students’ Perceptions of the Use of Student Worksheets in Speaking Skills in the Third Grade of Junior High School - Maujudatul Mufidah, Zahratul; Maziya Rizqi Yaumi, Nur Qodro (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2023)
The research questions in this research are as follow: 1) What are the students’ perceptions on use of Student worksheet in Speaking Skill at third grade of Junior High School? 2) What factors do influence the use of student worksheet in Speaking Skill at third grade of Junior High School?This research applied a qualitative descriptive as research method. It was conducted in Junior High School. The data were gathered by observation, interview, and document review. While, technique and data source triangulation were used to validate data. The result of this research indicated that there were a positive and negative perception based on the material and exercise in the student worksheet. First, for the students’ positive perceptions were: (a) students said that they become more active, enthusiast, and motivated in learning (b) it was easy for them to understand the material and also to do the task (b) the students can speak properly and correctly in learning by using the student worksheet. Second, for the students’ negative perceptions based on the material and exercise were: (a) the students cannot improve their vocabulary because most of the material is translated by the teacher and Google (b) the students cannot improve their speaking skill because the student worksheet not yet focus on speaking skill only (c) the students still mix English with indonesian or Javanese in the learning process. (d) the student worksheet not fulfill the students’ need in learning . While for the factors influence the use of student worksheet in speaking skill, the researcher found that most of the students agree that the internals factors contain: physiological and psychological. Meanwhile, the external factors contain environmental and instrumental factors influence the use of student worksheet in speaking skill.